Thyroid and Growth Hormones Interdependence and Their Synergistic Effect on Growth and Development at Childhood - Eworo, Raymond Ekong (Recent Developments in Medicine and Medical Research Vol. 10, 2021)
Aims: To investigate how variation in the plasma levels of thyroid and growth hormones influences the physical growth indices, and the variation of these hormones with age in children aged 6-10 years. Study Designed: The study is a prospective study, designed to investigate how variation in growth and thyroid hormones relate to physical growth and development in children. Methodology: Anthropometric uniqueness were described and Body Mass Index computed for 180 (male 81 and female 99) participants of the study. The children were categorized further based on age into 6, 7, 8, 9, and 10 years. Thyroid and growth hormones were determined by Enzyme-Linked Immunosorbent Assay (ELISA) specific for the various hormones, using STAT FAX 303 microtitre plate reader. Statistical analysis, data management and statistical analyses were performed using SPSS version 23.0 (SPSS, Chicago, IL, USA) statistical package. Difference between groups was determined using Student’s t-test, variations among groups by ANOVA and relationship between parameters using Pearson’s correlation. Excel was used to chart the relationship between the concentrations of the hormones against the ages of the children. The significance level of the tests was set at \(α\)=0.05. Results will be expressed as Mean ± SD Results: Nineteen percent (n=34) had GH values (\(\le\)0.6 ng/ml), lower than the expected normal, 64% (n=115) had values between (0.6-10.0ng/ml) while 17% (n=31) had values \(\ge\)10.0 ng/ml. Ninety two percent (n=166) of the children had thyroid stimulating hormone (TSH) values between 0.35-8.44 \(μ\)Iu/ml; 6.1% (n=11) had values >8.44 \(μ\)Iu/ml which are above normal while1.7% (n=3) had values <0.35 \(μ\)Iu/ml lower than normal. Triiodothyronine appears to increase from birth recording a peak within the first year of postnatal life, and then progressively declining to adult values while GH increases from birth attaining a peak about the age of nine then falling progressively to adult values. Children with apparent GH deficiency had significantly higher T3 and T4 levels and lower TSH, those with high GH values had correspondingly low T3 and T4 values and high TSH. The correlation coefficients of TSH and growth hormones in those with high and low GH (r=-0.05 and r=-0.130) respectively were both negative while that of TSH and GH in those with normal GH was positive (r=0.093), however, physical growth indexes are preserved across board. Conclusion: It was concluded from the study that growth failure may be due to failure of both hormones and may likely not occur when an unbroken synergy exist between thyroid and growth hormones during childhood.